2018
DOI: 10.4103/0366-6999.222337
|View full text |Cite
|
Sign up to set email alerts
|

Advances of Long Noncoding RNAs-mediated Regulation in Reproduction

Abstract: Objective:Advances in genomics and molecular biology have led to the discovery of a large group of uncharacterized long noncoding RNAs (lncRNAs). Emerging evidence indicated that many lncRNAs function in multiple biological processes and its dysregulation often causes diseases. Recent studies suggested that almost all regulatory lncRNAs interact with biological macromolecules such as DNA, RNA, and protein. LncRNAs regulate gene expression mainly on three levels, including epigenetic modification, transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 76 publications
(73 reference statements)
0
30
0
Order By: Relevance
“…Within these ECRs are DNA methylation epimutations and long non-coding RNA (ncRNA) expression sites [ 114 ]. The long ncRNAs play a role in regulation of distal gene transcription and epigenetic regulation [ 115 , 116 ]. Observations suggest that within an ECR many of the genes are epigenetically regulated up or down as a block.…”
Section: Transgenerational Gene Expression Changesmentioning
confidence: 99%
“…Within these ECRs are DNA methylation epimutations and long non-coding RNA (ncRNA) expression sites [ 114 ]. The long ncRNAs play a role in regulation of distal gene transcription and epigenetic regulation [ 115 , 116 ]. Observations suggest that within an ECR many of the genes are epigenetically regulated up or down as a block.…”
Section: Transgenerational Gene Expression Changesmentioning
confidence: 99%
“…Recent studies propose lncRNAs as players in regulation of gene expression in immune cells and in a variety of human diseases, including cancers. Indeed, lncRNAs are involved in cancer development through different pathways; specifically, their deregulation induces cancer cells to initiate tumor growth and metastatic processes [65]. Various evidences have indicated that several lncRNA contribute to cancer cell phenotypes through the interaction with chromatin-modifying agents and proteins, such as the polycomb repressive complex 2, LSD1, CoREST, and SMCX.…”
Section: Lsd1 and Lncrnamentioning
confidence: 99%
“…Recently, emerging evidence revealed that a large number of lncRNAs are widely involved in regulating the development of the reproduction system [ 35 ]. However, there is still a lack of studies on the role of lncRNAs in the formation of male germ cells.…”
Section: Discussionmentioning
confidence: 99%